LOFAR discovery of a quiet emission mode in PSR B0823+26 - Sobey, Charlotte; Young, N.; Hessels, J.; Weltevrede, P.; Noutsos, A.; Stappers, B.; Kramer, M.; Bassa, C.; Lyne, A.; Kondratiev, V.; Hassall, T.; Keane, E.; et al. (Oxford University Press, 2015)
PSR B0823+26, a 0.53-s radio pulsar, displays a host of emission phenomena over time-scales of seconds to (at least) hours, including nulling, subpulse drifting, and mode-changing. Studying pulsars like PSR B0823+26 provides further insight into the relationship between these various emission phenomena and what they might teach us about pulsar magnetospheres. Here we report on the LOFAR (Low-Frequency Array) discovery that PSR B0823+26 has a weak and sporadically emitting 'quiet' (Q) emission mode that is over 100 times weaker (on average) and has a nulling fraction forty-times greater than that of the more regularly-emitting 'bright' (B) mode. Previously, the pulsar has been undetected in the Q mode, and was assumed to be nulling continuously. PSR B0823+26 shows a further decrease in average flux just before the transition into the B mode, and perhaps truly turns off completely at these times. Furthermore, simultaneous observations taken with the LOFAR, Westerbork, Lovell, and Effelsberg telescopes between 110 MHz and 2.7 GHz demonstrate that the transition between the Q mode and B mode occurs within one single rotation of the neutron star, and that it is concurrent across the range of frequencies observed. © 2015 The Authors.